Enaminones in a multicomponent synthesis of 4-aryldihydropyridines for potential applications in photoinduced intramolecular electron-transfer systems - Al-Awadi, Nouria A.; Ibrahim, Maher R.; Elnagdi, Mohamed H.; John, Elizabeth; Ibrahim, Yehia A. (Beilstein Journal of Organic Chemistry, 2012)
An efficient three component reaction with enaminones, primary amines and aldehydes resulted in easy access to 1,4-dihydropyridines with different substituents at the 1-, 3-, 4- and 5-positions. Microwaves improved the reaction yield, reducing also considerably the reaction time and the amount of solvent used. Chiral primary amines gave chiral 1-substituted-1,4-dihydropyridines. The 4-(1-naphthyl) and 4-(phenanthren-9-yl)dihydropyridine derivatives exhibited an interesting photoluminescence behavior, which suggests their potential application as suitable photoinduced intramolecular electron-transfer systems.
Keywords: enaminones; 1,4-dihydropyridines; microwaves; multi-component reactions; photoluminescence